Os sistemas públicos de comunicação e a política : o contexto econômico e político das emissoras públicas brasileiras – o caso Aperipê - Pinheiro, Werden Tavares (2015)
Our research seeks to do a reading of the transformations undergone by the Brazilian public communication system. Therefore, we seek to understand the public broadcasters as part of the market structure, next to the trade. In this perspective, we try to discuss the function of each type of public broadcasters field, its chronology and its historical use by politicians, but also its relationship with the private field and with the audience. We, on the other hand, a historical listing the policy to events that are part of the narrative of Brazilian public broadcasters. The survey included interviews and a thorough analysis of documents, laws and printed. As a case study, we chose to focus on the history of Aperipê Sergipe Foundation, trying to understand how the Management, Structure and Popular Participation in the Sergipe public broadcasting system. In other words, we aim to understand the structure and point out its contradictions, approaching theory and reality, to discuss the importance of public media for society as a state instrument, its own definitions and reasons for being.